The role of glycogen phosphorylase in glycogen biogenesis in skeletal muscle after exercise - Abram Katz (Sports Medicine and Health Science, 2023)
Initially it was believed that phosphorylase was responsible for both glycogen breakdown and synthesis in the living cell. The discovery of glycogen synthase and McArdle's disease (lack of phosphorylase activity), together with the high Pi/glucose 1-P ratio in skeletal muscle, demonstrated that glycogen synthesis could not be attributed to reversal of the phosphorylase reaction. Rather, glycogen synthesis was attributable solely to the activity of glycogen synthase, subsequent to the transport of glucose into the cell. However, the well-established observation that phosphorylase was inactivated (i.e., dephosphorylated) during the initial recovery period after prior exercise, when the rate of glycogen accumulation is highest and independent of insulin, suggested that phosphorylase could play an active role in glycogen accumulation. But the quantitative contribution of phosphorylase inactivation was not established until recently, when studying isolated murine muscle preparations during recovery from repeated contractions at temperatures ranging from 25 to 35 °C. Thus, in both slow-twitch, oxidative and fast-twitch, glycolytic muscles, inactivation of phosphorylase accounted for 45%–75% of glycogen accumulation during the initial hours of recovery following repeated contractions. Such data indicate that phosphorylase inactivation may be the most important mechanism for glycogen accumulation under defined conditions. These results support the initial belief that phosphorylase plays a quantitative role in glycogen formation in the living cell. However, the mechanism is not via activation of phosphorylase, but rather via inactivation of the enzyme.